The Multifaceted Benefits of Leptin: Beyond Weight Regulation (Asian Journal of Pharmaceutics (AJP), 2024)
Leptin is a hormone that is produced by a variety of different cells, most notably adipocytes, but also by thestomach, lungs, and other organs, which mainly acts on the brain’s hypothalamus. Since its discovery in 1994,leptin’s pleiotropic activities have attracted increased interest from the scientific community. As a result, manypathological states have been related to leptin signaling disturbance. This includes the connection between one’snutritional state and one’s immune competence, which is one of the functions listed. It shares structural similaritieswith other inflammatory cytokines such as IL-6 and IL-12. Leptin regulates immunological responses, which isconsistent with its structure as a cytokine. Leptin’s most crucial physiological function is probably as a signal forthe transition between the fasted and fed states. Although leptin may play a role in preventing obesity in somepeople, the prevalence of obesity is strongly correlated with elevated leptin levels. There are no human studiesspecifically designed to investigate the role of leptin, despite numerous reports of connections between leptinlevels and various physiological and pathological states. In this review, the effect of leptin on different organsystems is described along with biology, mechanism of action, and its resistance factor.